Detecting undetectable — epidemiology, etiology, and diagnosis of carcinoma of unknown primary — systematic review - Ostojewska, Justyna; Wieczorek, Iga; Pachciński, Olaf; Zdziennicki, Wojciech; Burdan, Franciszek (Folia Medica Cracoviensia, 2023)
Carcinoma of unknown primary (CUP) is a heterogeneous group of oncological diseases in which it is impossible to determine the primary tumor. The incidence is 3–5% of oncologic patients, but the survival time varies from 6 weeks to 5 months. The diagnostics should begin with a clinical evaluation and basic laboratory tests. For CUP placed in head and neck the positron emission tomography — computed tomography is recommended; pancreatic or lung neoplasms are diagnosed with the computed tomography as well. Recently, the magnetic resonance, especially whole-body diffusion-weighted imaging has been introduced to the imaging panel. The lesion obtained during surgically removed metastases or biopsy material should be histopathological and mole-cularly examined to define the type of tumor. The basic immunoexpression panel should include cyto-keratin-5/6, -7 and -20, EMA, synaptophysin, chromogranin, vimentin and GATA3 and molecular ex-pression of ERBB2, PIK3CA, NF1, NF2, BRAF, IDH1, PTEN, FGFR2, EGFR, MET and CDK6. During the accurate diagnostics enable to classify malignancy of undefined primary origin as provisional CUP or finally confirmed CUP in which the primary place of tumor remains undetectable. The detailed diag-nostics should be performed in highly specified centers to establish an accurate diagnosis and to initiate personalized treatment. Majority of patients are diagnosed with adenocarcinoma (70%), undifferentiated carcinoma (20%), squamous cell or transitional cell/uroepithelial carcinoma (5–10%), neuroendocrine tumor (5%) and with minor incidence other histological types, including melanoma.
Keywords: cancer; carcinoma of unknown primary; metastases; diagnostics